Hemocyte density increases with developmental stage in an immune-challenged forest caterpillar. - Teresa M Stoepler (Public Library of Science (PLoS), 2013)
The cellular arm of the insect immune response is mediated by the activity of hemocytes. While hemocytes have been well-characterized morphologically and functionally in model insects, few studies have characterized the hemocytes of non-model insects. Further, the role of ontogeny in mediating immune response is not well understood in non-model invertebrate systems. The goals of the current study were to (1) determine the effects of caterpillar size (and age) on hemocyte density in naïve caterpillars and caterpillars challenged with non-pathogenic bacteria, and (2) characterize the hemocyte activity and diversity of cell types present in two forest caterpillars: Euclea delphinii and Lithacodes fasciola (Limacodidae). We found that although early and late instar (small and large size, respectively) naïve caterpillars had similar constitutive hemocyte densities in both species, late instar Lithacodes caterpillars injected with non-pathogenic E. coli produced more than a twofold greater density of hemocytes than those in early instars. We also found that both caterpillar species contained plasmatocytes, granulocytes and oenocytoids, all of which are found in other lepidopteran species, but lacked spherulocytes. Granulocytes and plasmatocytes were found to be strongly phagocytic in both species, but granulocytes exhibited a higher phagocytic activity than plasmatocytes. Our results strongly suggest that for at least one measure of immunological response, the production of hemocytes in response to infection, response magnitudes can increase over ontogeny. While the underlying raison d' être for this improvement remains unclear, these findings may be useful in explaining natural patterns of stage-dependent parasitism and pathogen infection.